Develop a mobile-first educational tool for university students - Koh, Swee Sen (Nanyang Technological University, 2022)
In the recent 10 to 15 years, smartphones have improved dramatically and are capable of taking on more sophisticated tasks. Students today spent a lot of their time on their smartphones for a wide variety of purposes including entertainment and work. In spite of the popularity of smartphones, many educational tools in the market for tertiary education focus on providing good user experience on the desktop browser and are not optimized for mobile learning. This project aims to explore this gap in the market by attempting to develop a suite of softwares which can be used by educators in tertiary education to provide high quality educational content for their students which are highly optimized for mobile learning. Additionally, using the developed software, this project also aims to have a real-world test of the software by using them to deliver the NTU CZ1013 (Physics for Computing) course.